2020
DOI: 10.11606/s1518-8787.2020054001540
|View full text |Cite
|
Sign up to set email alerts
|

Major depressive episode among university students in Southern Brazil

Abstract: INTRODUCTION: Depression is the leading cause of disability around the world, and it has been increasingly affecting young people. This study evaluates the prevalence and factors associated with major depression in university students, with emphasis on the influence of the academic field, chosen study area and the environment they are inserted. METHODS: A census of students who entered the university in the first semester of 2017 was held at a university in Southern Brazil. The outcome of major depressive epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
4
18
1
10
Order By: Relevance
“…In terms of health variables, in the current study, students with high depressive symptoms were significantly more likely to report ever IDU (AOR 1.82, P = 0.004). We agree with others, where among university students in Brazil, IDU was positively associated with major depressive episode [ 101 ]; and having higher depressive symptoms score was associated with ever IDU among students in North Kosovo [ 102 ]. Others found that the presence of psychiatric disorders was positively associated with the extent of illicit substance use [ 93 ].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of health variables, in the current study, students with high depressive symptoms were significantly more likely to report ever IDU (AOR 1.82, P = 0.004). We agree with others, where among university students in Brazil, IDU was positively associated with major depressive episode [ 101 ]; and having higher depressive symptoms score was associated with ever IDU among students in North Kosovo [ 102 ]. Others found that the presence of psychiatric disorders was positively associated with the extent of illicit substance use [ 93 ].…”
Section: Discussionsupporting
confidence: 88%
“…Depression was the dependent variable, while demographic and clinical variables that significantly associated with depression in univariate analysis were the independent variables. In addition, commonly reported associated factors of depression among university students, such as gender 42 , major subject 54 , family history of mental disorders 55 were entered as the independent variables.…”
Section: Assessment Instruments and Evaluation A Paper-and-pen Versimentioning
confidence: 99%
“…Dentre os hábitos prejudiciais está o consumo de álcool. Dos estudos analisados, em seis deles (Santangelo, 2018;Flesch et al, 2020;Piumatti, 2018;Hambisa, 2020;Tuyen, 2019;Ruisoto et al, 2016), esse hábito está associado significativamente a um risco aumentado de sintomas depressivos que pode ser atribuído à mudança no estilo de vida dos estudantes. Além do consumo de álcool, o tabagismo está associado com a diminuição da qualidade de vida relacionada à saúde dos estudantes universitários, resultando em níveis mais altos de sintomas depressivos (Milic et al, 2020).…”
Section: Discussionunclassified
“…Os alunos que fizeram o uso de substâncias ilícitas mostraram predisponência para a depressão (Piumatti, 2018). No estudo de Flesh et al 2020 Quanto ao sexo, diante dos dados analisados, as mulheres apresentam maior prevalência de depressão, sendo evidente que o sexo feminino está mais propenso ao desenvolvimento de sintomas depressivos (Santangelo, 2018;Hakami, 2018;Fernandes et al, 2018;Rossi et al, 2019;Lee, 2019;Nahas et al, 2019;Flesch et al, 2020). De acordo com Hakami, (2018) e Nahas et al (2019), as diferenças de gênero na prevalência de problemas de saúde mental podem ser explicadas por fatores psicossociais e biológicos, devido, por exemplo, à maior sensibilidade às relações interpessoais, bem como às alterações hormonais.…”
Section: Discussionunclassified
See 1 more Smart Citation